An Assessment of Sanitation Facilities in Places of Worship in Samarinda City - Fitrah, Muhammad Aidil; Rachmawati, Ayudhia; Elvira, Vivi Filia (Panakeia Journal of Epidemiology, 2025)
Places of worship are intensively used public facilities, and inadequate environmental quality may heighten the risk of disease transmission. Monitoring of sanitation compliance in such facilities remains limited, particularly in densely populated residential areas with greater environmental vulnerability. This study aimed to describe environmental health conditions and sanitation facilities in places of worship situated in densely populated areas of Samarinda City, Indonesia. A descriptive observational design was applied using a sanitation assessment checklist covering location, building conditions, clean water, wastewater disposal, solid waste management, latrine conditions, ventilation, lighting, and worship facilities. A total of 20 worship places were evaluated, and data were analyzed descriptively using frequencies, percentages, and mean scores. Results showed that all sites (100%) achieved scores ≥7000, indicating compliance with sanitation requirements, with an average score of 12,535. Clean water availability, flooring, wall conditions, and ventilation were the best-performing aspects (100%). However, deficiencies were observed in lighting (80%), sealed wastewater channels (65%), and standardized temporary waste storage (50%). Overall, sanitation conditions were good, although improvements in lighting and waste management remain necessary.